Networked Teacher Professional Development: Applying the Networked Learning Framework to Online Teacher Professional Development - Ostashewski, Nathaniel; Reid, D. (International Council for Open and Distance Education, 2010)
This paper describes a design-based research program examining online teacher professional development (oTPD) activities delivered in a social networking site. Introduced in this paper is the Networked Learning Framework (NLF), an instructional design model for learning within a social networking site. One implementation of the NLF, technology Courselets delivered in a social networking site for Alberta teachers, is described in detail. Teachers report that reflective blogs and collegial discussions are valuable when supported by social networking and Web 2.0 tools. There has been little research into the design of educational opportunities delivered within a social networking environment and the NLF is an attempt to investigate this phenomenon. As a result of this research, seven design principles were identified to assist in the development of networked teacher professional development (nTPD). Further research to identify effective supports for social networking novices and ways to inspire teacher confidence in online collaborations is needed.